Anchoring, Reference Prices, and List Price Collusion - Johannes Paha (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
The firms in this model set non-binding list prices before competing for buyers by non-cooperatively granting discounts. Each firm has an incentive to set a high list price if, for example, the customers anchor their willingness-to-pay on the list price. However, list price competition occurs if customers are loss-averse with respect to firms charging above-average list prices. The firms may thus find agreements on higher list prices profitable, even if they continue granting discounts non-cooperatively. Most importantly, for being an equilibrium of the game, such agreements do not require a dynamic game or mutual monitoring of the list prices.
Keywords: D90; D91; K21; L41; M30; 330; Anchoring; behavioral industrial organization; collusion; list price; loss aversion; reference price